Defibrillation and external pacing in flight: incidence and implications. Issue 1 (22nd December 2012) - Daly, Stuart; Milne, Helen J; Holmes, Dan P; Corfield, Alasdair R
Abstract : Introduction: Emergency electrical intervention for patients in the form of defibrillation, cardioversion and external cardiac pacing can be life saving. Advances in medical technology have enabled electrical intervention to be delivered from small, portable devices. With the rising use of air transport for patients, electrical intervention during aeromedical transfer has an increasing incidence. Our aim was to describe the incidence of electrical intervention in a cohort of critically ill patients undergoing aeromedical transfer and review the risks associated with electrical intervention. Methods: All secondary retrievals undertaken by a national aeromedical critical care retrieval service were reviewed over a 48-month period. Results: In a mixed medical and trauma critical care population, 11 of 967 (1.1%) secondary retrievals required electrical intervention during aeromedical critical care retrieval. The median age of these patients was 77 years (range 32–86) and the median transport time was 70 min (range 40–100 min). All of these patients had an underlying primary cardiac condition and had been identified as high risk for developing an arrhythmia. Conclusions: Electrical intervention in a transport environment brings unique challenges, particularly during aeromedical transport. Our study in a European model shows that there is a small but significant incidence of electrical intervention required during aeromedical flight for critically ill patients. There are potential safety issues with electrical intervention in aeromedical flight; therefore, any service involved in the transport of critically ill patients needs to have a robust procedure in place to deliver this safely.